Identification and Analysis of GhEXO Gene Family Indicated That GhEXO7_At Promotes Plant Growth and Development Through Brassinosteroid Signaling in Cotton (Gossypium hirsutum L.) - Li, Shengdong; Liu, Zhao; Chen, Guoquan; Qanmber, Ghulam; Lu, Lili; Zhang, Jiaxin; Ma, Shuya; Yang, Zuoren; Li, Fuguang (Frontiers in Plant Science, 2021)
Brassinosteroids (BRs), an efficient plant endogenous hormone, significantly promotes plant nutrient growth adapting to biological and abiotic adversities. BRs mainly promote plant cell elongation by regulating gene expression patterns. EXORDIUM (EXO) genes have been characterized as the indicators of BR response genes. Cotton, an ancient crop, is of great economic value and its fibers can be made into all kinds of fabrics. However, EXO gene family genes have not been full identified in cotton. 175 EXO genes were identified in nine plant species, of which 39 GhEXO genes in Gossypium hirsutum in our study. A phylogenetic analysis grouped all of the proteins encoded by the EXO genes into five major clades. Sequence identification of conserved amino acid residues among monocotyledonous and dicotyledonous species showed a high level of conservation across the N and C terminal regions. Only 25% the GhEXO genes contain introns besides conserved gene structure and protein motifs distribution. The 39 GhEXO genes were unevenly distributed on the 18 At and Dt sub-genome chromosomes. Most of the GhEXO genes were derived from gene duplication events, while only three genes showed evidence of tandem duplication. Homologous locus relationships showed that 15 GhEXO genes are located on collinear blocks and that all orthologous/paralogous gene pairs had Ka > Ks values, indicating purifying selection pressure. The GhEXO genes showed ubiquitous expression in all eight tested cotton tissues and following exposure to three phytohormones, IAA, GA, and BL. Furthermore, GhEXO7_At was mainly expressed in response to BL treatment, and was predominantly expressed in the fibers. GhEXO7_At was found to be a plasma membrane protein, and its ectopic expression in Arabidopsis mediated BR-regulated plant growth and development with altered expression of DWF4, CPD, KCS1, and EXP5. Additionally, the functions of GhEXO7_At were confirmed by virus-induced gene silencing (VIGS) in cotton. This study will provide important genetic resources for future cotton breeding programs.